2019
DOI: 10.1021/acs.jpcb.9b01665
|View full text |Cite
|
Sign up to set email alerts
|

Pseudopeptide Designed to Inhibit Oligomerization and Redox Chemistry in Alzheimer’s Disease

Abstract: Aggregation of amyloid beta peptide (Aβ) and inflammatory processes associated with the generation of superoxide, hydrogen peroxide, and hydroxyl radicals are responsible for neurotoxicity in Alzheimer’s disease. The latter are a result of the redox activity of copper-bound Aβ complexes with molecular oxygen. A ligand (PI1), previously designed to compete with Aβ for copper, and a pseudopeptide (SGC1) with a property of breaking the self-aggregation of Aβ, are attached to each other to form a new pseudopeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Although the pathological mechanisms underlying AD remain controversial, Aβ peptide is believed to be the central participant. Recently, Opare ( Opare and Rauk, 2019 ) and Samanta ( Samanta et al., 2019 ) demonstrated that Aβ-related peptides were the initiators of AD, and the imbalance between Aβ accumulation and clearance was the main cause of AD. The drugs currently approved for clinical treatment of AD are based on neuroprotective agents (e.g., neurotransmitter generators or neurotransmitter receptor agonists/antagonists).…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathological mechanisms underlying AD remain controversial, Aβ peptide is believed to be the central participant. Recently, Opare ( Opare and Rauk, 2019 ) and Samanta ( Samanta et al., 2019 ) demonstrated that Aβ-related peptides were the initiators of AD, and the imbalance between Aβ accumulation and clearance was the main cause of AD. The drugs currently approved for clinical treatment of AD are based on neuroprotective agents (e.g., neurotransmitter generators or neurotransmitter receptor agonists/antagonists).…”
Section: Introductionmentioning
confidence: 99%